(untitled) (Proceeding of the International Conference on Arts and Humanities, 2021)
Emotional intelligence refers to the ability to identify, evaluate, control and express emotions in various situations. It can be categorised to five essential elements which consists of: Self Awareness, Self-Regulation, Motivation, Empathy and Social Skills. For children, emotional intelligence is important as it can improve their self-awareness, manage their stress, build empathy, and communicate effectively as well as making good decisions. This study will explore the correlation between children and smartphone addiction with their emotional intelligence. Three psychology laboratories/experiments were conducted using multi video recorder and recording devices from different angles to observe the behaviours of five children aged five to nine years old in two situations: the one with the present of smartphone and without the smartphone. Results showed that children display more interest in communicating, playing, creating conversations, and are more cheerful without the present of a smartphone. The children have the potential in socializing, were aware about their surroundings and show more empathy when they are not encircled with smartphones. The result from this behaviour study may create awareness of the impact of smartphone addiction among children and to increase understanding and concern for the emotional intelligence of the children who are growing up with the luxury of having smartphones.